Complete genome sequence of a multi‐recombinant echovirus 6 strain isolated from CSF in Ahvaz, Southwestern Iran. Issue 4 (April 2018) - Abbasi, Samaneh; Makvandi, Manoochehr; Teimoori, Ali; Samarbaf‐Zadeh, Alireza
Abstract : Background: : Echovirus 6 (E6), is one of the main enteroviral serotypes, was initially isolated from patients with aseptic meningitis (AM) and is a major cause of hospitalization among children and adults worldwide. Methods: : A cerebrospinal fluid (CSF) sample was collected from patient with clinically suspected aseptic meningitis (AM) in August 2011. Following detection of a virus and subsequent virus serotyping, the whole genome sequence was determined. The sequence of the VP1 region of the isolated strain E6 RA/E6/Ahvaz/Iran/2011 showed 79% (>75%) nucleotide and 94% (>85%) amino acid homology with prototype strain D'Amori. The isolated strain was identified as an E6 serotype. A specimen was cultured in a human rhabdomyosarcoma (RD) cell line. Following propagation, the virus was further analyzed using the plaque assay technique, reverse transcription PCR (RT‐PCR), rapid amplification of CDNA ends (RACE), TA cloning, sequencing, phylogenetic analysis, Simplot and boot scanning analyses (ver. 3.5) were applied to find evidence of recombination in the isolated strain. Results: : The isolated Echo6 strain RA/E6/Ahvaz/Iran/2011 has been recorded in GenBank with a partial and complete genome accession numbers (KX619440) (KX198605), respectively. The complete genomic sequence was 7435 nt, with a 742 bp 5′ UTR, 117 bp 3′ UTR, and an open reading frame (ORF) encoding a polypeptide of 2191 amino acids. The nucleotide analysis of the VP1 and structural genomic regions of the isolated strain showed high similarity with strain E6–10887–99 isolated from patient with facial nerve paresis in Russia in 1999. The recombinations evidence were observed in the isolated strain E6 RA/E6/Ahvaz/Iran/2011 and found to have a high levels of inter‐serotypic exchanges in 2C and 3A‐3C genomic regions with Echovirus13 and Echovirus14, respectively. Conclusion: : Full genome sequence analysis of enteroviral is required to understand the epidemiological pattern and to evaluate the new enterovirus circulating in community.